Hrabia Monte Christo - Dumas, Alexandre, 1802-1870.; Dumas, Alexandre, 1802-1870. (Warszawa : Iskry, 1991)
The classic tale of a man imprisoned for an unjust cause and his final revenge.
Translation of: Le comte de Monte-Cristo.